Exchange coupling and the grain boundary in magnetic nanocomposites - COEY, JOHN MICHAEL DAVID (IEEE, 1997)
The grain boundary phase/material found to be present in two-phase mechanically alloyed nanocomposites of Sm2Fel7N3/Fe and NdzFe14B/Fe was characterized using Mossbauer spectroscopy and magnetization measurements. The fraction of iron in this third component is typically 10-15% in Sm*Fel?Ns/Fe and 4-5% in Nd*Fe14B/Fe nanocomposites. The influence of the grain size of the nanocomposite and the grain boundary material on the susceptibility was studied and the results are discussed in terms of the model of Wang and Mills.
PUBLISHED
Keywords: Physics